KEPASTIAN HUKUM RELAKSASI DEBITUR BANK PERKREDITAN RAKYAT (BPR) DANA NUSANTARA AKIBAT PANDEMI COVID-19 - Desriwaty, Sari; Jamba, Padrisan (LPPM Universitas Putera Batam, 2022)
During the COVID-19 pandemic, the economic sector in Indonesia declined drastically, this significant impact also spread throughout the world. The decrease felt by banking institutions that channel debtor credit, because obligations that must be carried out for a certain period of time must be caused by a suspension issued by the Financial Services Authority. This credit relaxation may apply if the debtor submits an offer for credit relaxation. In the application of this credit suspension, there are also problems, of course, such as legal certainty and strength in the implementation of the suspension of debtors. The purpose of the research is to find out how the applicable legal arrangements are, to find out the obstacles and obstacles when offering a suspension. In this case, applying the normative juridical research method by referring to the defense of written legal rules, not only that this research also involves books and applicable legal arrangements.